Smart Home Kendali Lampu Rumah Berbasis Mikrontroler Arduino Menggunakan Smartphone Android - Alvendo Wahyu Aranski (Prosiding, 2022)
The use of inefficient home lights is often underestimated by some people. This often happens because of the public's indifference to leaving the lights on when they are not needed, without realizing it, the cost of electricity bills also increases. The reason is none other than trivial things, wherever you want to turn off/ on the lights in a room in the house, it will require someone to go to an electrical device, this’s what makes some people reluctant to turn off the lights and in the end the lights are not turned off and are left on. To make it easier for people to control lights, in this study, we will design a tool that can control Arduino Uno-based house lights using aSmartphone as a medium that will be used to control lights. Control is done through an application on a Smartphone. The application is made using the MIT APP IVENTOR software as an interface to control the on/off lights. The android smartphone sends data via Bluetooth which then the data will be received by the Bluetooth HC-05.